Inexpensive high‐precision system for measuring air pressure fluctuations - Manuel Mohr; Thomas Laemmel; Martin Maier; Dirk Schindler (Meteorological Applications, 2020)
Abstract Small air pressure fluctuations (amplitude <10 Pa, frequency range 0.01–0.1 Hz) were simultaneously measured using an inexpensive differential air pressure sensor system and a significantly more expensive high‐precision absolute air pressure sensor reference. The measured air pressure fluctuations were compared and analysed in the time domain and in the time–frequency domain using the wavelet transform. Our analyses demonstrate that there are no significant differences between the measuring results of the two systems. The inexpensive system measures air pressure fluctuations with the same precision as the reference sensor or even a higher precision. As an application, the pressure pumping co‐efficients were calculated from the air pressure fluctuations recorded by both systems. A comparison again showed that both evaluated air pressure sensors yield very similar results. Therefore, it is concluded that the inexpensive system is suitable for reliable air pressure fluctuation measurements.